Detection of CWD in cervids by RT-QuIC assay of third eyelids. - Sarah K Cooper; Clare E Hoover; Davin M Henderson; Nicholas J Haley; Candace K Mathiason; Edward A Hoover (PLoS ONE)
The diagnosis of chronic wasting disease (CWD) relies on demonstration of the disease-associated misfolded CWD prion protein (PrPCWD) in brain or retropharyngeal lymph node tissue by immunodetection methods, e.g. ELISA and immunohistochemistry (IHC). The success of these methods relies on a quality sample of tissues, which requires both anatomical knowledge and considerable dissection to collect. As the prevalence of CWD continues to increase globally, the development of fast and cost-effective methods to detect the disease is vital to facilitate CWD detection and surveillance. To address these issues, we have evaluated third eyelids from CWD-infected deer and elk using real-time quaking induced conversion (RT-QuIC). We identified prion seeding activity in third eyelids in 24 of 25 (96%) CWD-infected white-tailed deer (Odocoileus virginianus). We detected RT-QuIC positivity in the third eyelid as early as 1 month after experimental CWD exposure. In addition, we identified prion seeding activity in third eyelids of 18 of 25 (72%) naturally exposed asymptomatic CWD-positive rocky mountain elk (Cervus canadensis nelson). We compared CWD detection by RT-QuIC and IHC in third eyelid, retropharyngeal lymph node, and brain in 10 deer in early symptomatic stage of disease. IHC detected PrPCWD deposition in third eyelid lymphoid follicles in 5 of 10 deer (50%) whereas third eyelids of all 10 animals were positive by RT-QuIC. This difference reflected in part a lower requirement for lymphoid follicle presence for seeding activity detection by RT-QuIC. In conclusion, RT-QuIC analysis of the third eyelid, an easily accessed tissue, has potential to advance CWD detection and testing compliance.